OSTEOPOROSIS: ASSESSMENT OF A RISK FOR RECURRENT LOW-TRAUMA FRACTURES IN POSTMENOPAUSAL WOMEN - O. V. Dobrovolskaya; N. V. Toroptsova (Научно-практическая ревматология)
Objective: to assess a risk for new fractures in a cohort of postmenopausal women who have sustained low-trauma fractures, by using the FRAX® algorithm, and to compare the assessments with data on the fractures have occurred during a prospective follow-up study.Subjects and methods. The investigation enrolled 128 postmenopausal women (mean age, 64.9±8.3 years) who had sustained low-trauma fractures at five sites (the hip, forearm, humeral neck, vertebral column, and ankle). A ten-year fracture risk was assessed using the FRAX® algorithm with and without regard for bone mineral density (BMD). New osteoporotic fractures were recorded during a three-year prospective follow-up study.Results and discussion. The average FRAX® algorithm values for all new osteoporotic and hip fractures in the entire group were 18.0±5.6 and 3.7±3.7% (without consideration of BMD), 17.9±6.6 and 3.5±4.0% (with consideration of BMD) (p > 0.05). The true incidence of recurrent fractures over 3 years was 17.2%. During 3 years, the incidence of recurrent fractures in the women who had sustained low-trauma fractures of the proximal hip, humeral neck, and spinal column was 28.6, 25.0, and 22.8%, respectively, which exceeded the estimated 10-year fracture risk for these sites. The history of multiple low-trauma fractures versus single one increased the risk for subsequent fractures by 3.63 and 9.43 times among women with high or low estimated FRAX risk rate, respectively.Conclusion. The three-year prospective follow-up study has shown that the FRAX® algorithm underestimated the risk associated with the presence of recurrent fractures in the history; moreover, new fractures significantly more commonly occur in persons who have sustained low-trauma fractures in the proximal hip, humoral neck, and vertebral column.